INOVASI KUE LUMPUR SURGA DENGAN SUBSTITUSI TEPUNG MOCAF DAN PENAMBAHAN DAUN KELOR SEBAGAI JAJANAN SEHAT - Fajjar Harry Kurniawan; Ita Fatkhur Romadhoni; Ila Huda Puspita Dewi; Mafisa Restami (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This experimental research aims to determine the effect of modified cassava flour (MOCAF) substitution levels (25%, 50%, 75%) and the addition of moringa leaf powder (5%) on the organoleptic properties (color, aroma, texture, taste, overall preference) of lumpur surga cake. Data collection involved 30 semi-trained panelists using a 1-5 hedonic scale evaluation sheet. The data were analyzed quantitatively using One-Way ANOVA via SPSS version 29, followed by Duncan's test if significant effects were observed. The results showed a significant effect on the color and overall preference attributes, while aroma, texture, and taste showed no significant differences. The formulation with 75% MOCAF substitution was determined as the best product, obtaining the highest preference score (4.30). The application of thick coconut milk in this two-layer innovation effectively masked the earthy aroma of moringa and maintained a melting texture, making this product a potential healthy functional snack without eliminating its traditional flavor.